Analysis and assessment of heavy metals concentrations in Nemunas river bottom sediments at Alytus city territory - Valskys, Vaidotas; Valskienė, Roberta; Ignatavičius, Gytautas (Journal of Environmental Engineering and Landscape Management, 2015)
Concentrations and spatial distribution of heavy metals on the left and right banks of the river Nemunas bottom sediments are analyzed in this article. The research methodology of X-ray fluorescence spectrometry for bottom sediments and operating principles of XL2 spectrometer used for analysis are overviewed. The results of analysis are presented and compared with LAND 20-2005 requirements as well as studies that were carried out previously. The influence of Alytus city for Nemunas river sediments quality is assessed. Dischargers formed additional samples which were taken and included to the list of ordinary samples. The trend of heavy metals (Cd, Cu, Cr) concentrations showed the growth of pollution downstream the urban area. The estimated Zd (total pollution) values clearly indicated higher contamination by heavy metals on the left bank of Nemunas River. Extensive surveys of river sediments allow assessing the extent of anthropogenic impact, which can be harmful to the river ecosystem and human health.First published online: 28 Jan 2015